Real-Time Study of Rapid Spread of Antibiotic Resistance Plasmid in Biofilm Using Microfluidics - Li, Bing; Qiu, Yong; Zhang, Jing; Huang, Xia; Shi, Hanchang; Yin, Huabing (Environmental science & technology, 2018)
Gene transfer in biofilms is known to play an important role in antibiotic resistance dissemination. However, the process remains poorly understood. In this study, microfluidics with time-lapse imaging was used for real-time monitoring of plasmid-mediated horizontal gene transfer (HGT) in biofilms. Pseudomonas putida KT2440 harboring an antibiotic resistance plasmid RP4 was chosen as the donor while Escherichia coli and activated sludge bacteria were used as the recipient cells. Dynamic features of the transfer process, including the transfer rate, cell growth rate and kinetic changes of the transfer frequency, were determined. It was found that the routes for gene transfer strongly depend on the structure and composition of a biofilm. While intraspecies HGT is essential to initiate a transfer event, the secondary retransfer from transconjugants to the same species is more efficient and can cause cascading gene spread in single-strain biofilms. For the activated sludge biofilm, only small and scattered colonies formed and vertical gene transfer appears to be the dominant route after initial intraspecies transfer. Furthermore, more than 46% of genera in the activated sludge were permissive to plasmid RP4, many of which are associated with human pathogens. These phenomena imply early prevention and interruptions to biofilm structure could provide an effect way to inhibit rapid antibiotic resistance gene spread and reduce the likelihood of catastrophic events associated with antibiotic resistance.